Robotic Rehabilitation: An Opportunity to Improve Cognitive Functions in Subjects With Stroke. An Explorative Study - Aprile, Irene; Guardati, Giulia; Cipollini, Valeria; Papadopoulou, Dionysia; Mastrorosa, Alessia; Castelli, Letizia; Monteleone, Serena; Redolfi, Alessandra; Galeri, Silvia; Germanotta, Marco (Frontiers in Neurology, 2020)
Background: After a stroke, up to three-quarters of acute and subacute stroke survivors exhibit cognitive impairment, with a significant impact on functional recovery, quality of life, and social engagement. Robotic therapy has shown its effectiveness on motor recovery but its effectiveness on cognitive recovery has not fully investigated. Objective: This study aims to assess the impact of a technological rehabilitation intervention on cognitive functions in patients with stroke, using a set of three robots and one sensor-based device for upper limb rehabilitation. Methods: This is a pilot study in which fifty-one patients were enrolled. An upper limb rehabilitation program was performed using three robots and one sensor-based device. The intervention comprised motor/cognitive exercises, specially selected among the available ones to train also cognitive functions. Patients underwent 30 rehabilitation sessions, each session lasting 45 minutes, 5 days a week. Patients were assessed before and after the treatment with several cognitive tests (Oxford Cognitive Scale, Symbol Digit Modalities Test, Digit Span, Rey-Osterrieth Complex Figure, Tower of London, and Stroop test). In addition, motor (Fugl-Meyer Assessment and Motricity Index) and disability (modified Barthel Index) scales were used. Results: According to the Oxford Cognitive Scale domains, a significant percentage of patients exhibited cognitive deficits. Excluding perception (with only one patient impaired), the domain with the lowest percentage of patients showing a pathological score was praxis (about 25%), while the highest percentage of impaired patients was found in calculation (about 70%). After the treatment, patients improved in all the investigated cognitive domains, as measured by the selected cognitive assessment scales. Moreover, motor and disability scales confirmed the efficacy of robotics on upper limb rehabilitation in patients with stroke. Conclusions: This explorative study suggests that robotic technology can be used to combine motor and cognitive exercises in a unique treatment session. Clinicaltrials.gov: https://clinicaltrials.gov/ct2/show/NCT04164381